Abstract journal preparation on a micro: Yugoslavia's bulletin scientifique - Zajec, Jasenka (Array, 1990)
In this scientific paper the principles of computerized preparation of the abstracts for scientific journals are defined, and implemented on a journal Yugoslavia's bulletin scientifique, the scientific journal of the former Yugoslav (later on: Croatian) Academy of Sciences and Arts.